PENGARUH GAYA KEPEMIMPINAN DAN KETERLIBATAN KERJA TERHADAP KINERJA PEGAWAI KANTOR DPRD KAB. OGAN KOMERING ULU - Dewi, Rosmala; Natalia, Titie Syahnaz; Sari, Kartini Mayang (Ekonomika, 2024)
This research discussed the Influence of Leadership Style and Work Involvement on the Performance of DPRD Office Employees, Ogan Komering Ulu Regency. The population in this study were 63 employees of the DPRD Office of Ogan Komering Ulu Regency. The analytical method used was quantitative method using Multiple Linear Regression analysis tool. The results of the analysis explained that the t-count of each Leadership Style variable (X1) was 5.881 and Work Involvement (X2) was 7.023, which was greater than the t-table value of 2.00030 which stated that all variables had a significant influence on the Performance of Regency DPRD Office Employees. Ogan Komering Ulu. The calculated F value of 100.601 was greater than the F table of 3.15 which stated that together Leadership Style and Work Involvement had a significant influence on the Performance of Regency DPRD Office Employees. Ogan Komering Ulu. The value of the coefficient of determination (R Square) of 0.770 meant that in this case the contribution of the influence of Leadership Style and Work Involvement on Employees' Performance was 77%, while the remaining 23% was influenced by other variables outside of the variables included in this research model, namely work motivation, responsibility, work discipline and incentives.